The Bode Family of Large Language Models: Investigating the Frontiers of LLMs in Brazilian Portuguese - Paiola, Pedro Henrique; Garcia, Gabriel Lino; Correia, João Vitor Mariano; Manesco, João Renato Ribeiro; Garcia, Ana Lara Alves; Papa, João Paulo (Journal of the Brazilian Computer Society, 2025)
The rapid advancement of Large Language Models (LLMs) has significantly impacted Natural Language Processing, yet their effectiveness remains uneven across languages. Most state-of-the-art models are trained predominantly in English, leading to performance disparities in lower-resource languages such as Brazilian Portuguese (BP). This paper explores fine-tuning strategies for adapting open-weight LLMs to BP, focusing on dataset translation techniques, linguistic adaptation challenges, and parameter-efficient fine-tuning methods, such as LoRA and Q-LoRA. We present a benchmark analysis evaluating multiple fine-tuning approaches across various open models, establishing a guiding framework for future BP-specific adaptations. Our results showcase the importance of specialized fine-tuning in improving cross-lingual transfer and NLP performance in BP, contributing to the broader goal of enhancing multilingual language model accessibility.